Dabigatran versus vitamin k antagonist: an observational across‐cohort comparison in acute coronary syndrome patients with atrial fibrillation. (19th January 2018) - Gaubert, M.; Resseguier, N.; Laine, M.; Bonello, L.; Camoin‐Jau, L.; Paganelli, F.
Abstract : Essentials Acute coronary syndrome (ACS) with atrial fibrillation (AF) is a therapeutic challenge. Dual and triple antithrombotic therapy showed a similar thrombotic risk in ACS patients with AF. The omission of aspirin during the first month did not increase the rate of ischemic events. Replacement of vitamin K antagonist by dabigatran leads to an increased thrombotic risk. Summary: Background: Dual antithrombotic therapy comprising a vitamin K antagonist (VKA) plus clopidogrel reduces the incidence of major bleeding compared with triple therapy (VKA + clopidogrel + aspirin) in acute coronary syndrome (ACS) patients with atrial fibrillation (AF), with a similar thrombotic risk. The oral thrombin inhibitor dabigatran (150 mg twice a day) showed superiority over VKA in non‐valvular AF, but data supporting its use in AF patients presenting with ACS are limited. Objective: We sought to evaluate the efficacy of dabigatran vs. VKA in the management of AF patients undergoing percutaneous coronary intervention for an ACS. Methods: In this open‐label study, 133 consecutive patients received dabigatran plus clopidogrel. Another cohort of 133 patients treated with VKA plus clopidogrel was used as the control group. Results: After propensity score adjustment, the cumulative incidence of major adverse cardiovascular events over 24 months was higher with dabigatran vs. VKA (adjusted hazard ratio, 2.28; 95% confidence interval, 1.46–3.56). Similar rates of major bleeding were found (adjusted hazard ratio, 1.17; 95% confidence interval, 0.46–2.96). Conclusions: In AF patients presenting with ACS, replacement of VKA by dabigatran concurrently with clopidogrel is associated with an increased thrombotic risk, without a reduction in major bleeding.